Long term evolution coexistence with wireless fidelity in unlicensed spectrum using modified blank subframe allocation technique (2020)
In recent times, there has been an exponential increase in the use of mobile wireless devices such as smartphones, tablets etc. This has in turn led to a matching increase in demand for mobile broadband data usage. Many technologies have been engaged in order to meet this enormous data need. Long Term Evolution (LTE) and Wireless Fidelity (Wi-Fi) are major technologies used in meeting this high data demand. However, LTE was designed to operate in the licensed spectrum as a schedule-based technology in which the Evolved Node B (eNodeB) allots time-slots to devices in its cell. The licensed spectrum is more expensive to maintain for service providers and with increase in mobile wireless devices that same licensed spectrum is more congested. Operation of LTE in Unlicensed spectrum has been proposed as a solution to this need. However, if LTE operates in the unlicensed spectrum in its native form, Wi-Fi and other legacy technologies operating in the unlicensed spectrum get deprived of channel access. In this paper, we proposed a modified Blank Subframe Allocation technique in combination with Listen before talk (LBT) Clear Channel Assessment (CCA) before allocating the spectrum to its users to give channel access opportunity to Wi-Fi devices. Simulation was conducted for both instances i.e. when LTE operates with only Blank Subframe Allocation (BSA) coexistence and when CCA is applied to the LTE node. Performances of both models were evaluated using performance matrices such as delay time and throughput. The results showed that the proposed model achieved a smaller delay time than the existing model.